Enhancing cDC1-mediated anti-tumor immunity limits tumor progression and potentiates anti-PD-1 therapy in intrahepatic cholangiocarcinoma - Pei, Dong-Ni; Song, Yang; Zhou, Ying-Xia; Shu, Bo; Huang, Shao-wei; Li, Fa-Zhao; Dai, Wei-Dong; Sun, Bao-Ye (Frontiers in Immunology, 2025)
PurposeConventional type 1 dendritic cells (cDC1s) mastermind anti-cancer immunity and play a pivotal role in determining the efficacy of cancer immunotherapies. In this study, we sought to decipher the dynamic changes in the tumor immune landscape during intrahepatic cholangiocarcinoma (iCCA) development and harness the therapeutic potential of targeting cDC1s for cancer therapy.MethodsWe constructed spontaneous murine iCCAs via hydrodynamic tail vein injection (HDTVi) of plasmids encoding AKT/YAP. To characterize tumor-infiltrating immune cell populations throughout iCCA carcinogenesis and progression, we performed time-of-flight mass cytometry (CyTOF). To expand and activate cDC1s, we combined Flt3L with poly I:C (FL-pIC) therapy and assessed its therapeutic efficacy in both AKT/YAP-induced iCCAs and a subcutaneous tumor injection model. Flow cytometric analyses were used to evaluate intra-tumoral infiltration levels of cDCs and CD8+ T cells.ResultsCyTOF analysis revealed the progressive formation of an immunosuppressive tumor microenvironment as iCCA advances. Crucially, infiltration of cDC1s dramatically decreases in advanced iCCAs compared to early-stage tumors. Combined FL-pIC therapy preferentially expanded CD103+ cDC1s, powerfully inhibiting tumorigenesis in AKT/YAP-driven murine iCCAs and sensitizing these tumors to anti-PD-1 therapy. Moreover, FL-pIC therapy markedly suppressed the growth of established mIC-23 subcutaneous tumors.ConclusionsOur findings demonstrate that recruiting and activating intra-tumoral cDC1s is feasible and essential for driving anti-tumor CD8+ T cell immune responses and enhancing anti-PD-1 therapeutic effectiveness in iCCA.